2009
DOI: 10.1152/ajpcell.00272.2008
|View full text |Cite
|
Sign up to set email alerts
|

Green tea (−)-epigallocatechin gallate inhibits insulin stimulation of 3T3-L1 preadipocyte mitogenesis via the 67-kDa laminin receptor pathway

Abstract: Insulin and (-)-epigallocatechin gallate (EGCG) have been reported to regulate fat cell mitogenesis and adipogenesis, respectively. This study investigated the pathways involved in EGCG modulation of insulin-stimulated mitogenesis in 3T3-L1 preadipocytes. EGCG inhibited insulin stimulation of preadipocyte proliferation in a dose- and time-dependent manner. EGCG also suppressed insulin-stimulated phosphorylation of the insulin receptor-beta, insulin receptor (IR) substrates 1 and 2 (IRS1 and IRS2), and mitogen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 51 publications
6
52
0
1
Order By: Relevance
“…Previous studies reported that treatment of 3T3-L1 cells with EGCG leads to a reduction in cell number Ku et al, 2009;Wu et al, 2005). Consistently, our findings show that EGCG exerts a suppressive effect on the proliferative rate of cell cultures in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that treatment of 3T3-L1 cells with EGCG leads to a reduction in cell number Ku et al, 2009;Wu et al, 2005). Consistently, our findings show that EGCG exerts a suppressive effect on the proliferative rate of cell cultures in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that a 67-kDa laminin receptor (67LR), as the cell surface EGCG receptor, may be involved in mediating these actions of EGCG (22)(23)(24)(25). Moreover, EGCG is also believed to exert an Epigallocatechin-3-gallate prevents TNF-α-induced NF-κB activation thereby upregulating ABCA1 via the Nrf2/Keap1 pathway in macrophage foam cells anti-atherosclerotic effect via anti-inflammatory and metabolic regulation activities (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this receptor has also been shown to be responsible for antiallergic effects of EGCG in basophils (26,27). In preadipocytes, EGCG has been reported to mediate anti-insulin signaling via the 67LR pathway (28). However, it is not clear whether EGCG action through 67LR involves the negative regulatory effect of EGCG for inflammatory responses.…”
mentioning
confidence: 99%